D’une éthique de la traduction : Assia Djebar ou les apories de l’écriture en langue française - Hervé Sanson (Multilinguales)
Writing in French language for Assia Djebar has always been an aporia : how, form the Berber or Arabic sounds, to translate in the language of the other former colonizer, the calls, the complaints, the tears, the hopes and the sufferings of his fellow countrymen, his ancestors? How to protect in the French language scorias, peculiarities of the language of origin ? Because Djebar is exactly tuned to the difference of the language, of languages : she makes listen under the language of writing the breath, the rhythm of the mother tongues, and develops consequently a real “poetics of translation”, to quote Henri Meschonnic.